The role of psycholinguistics for language learning in teaching based on formulaic sequence use and oral fluency - Yu, Yue (Frontiers in Psychology, 2022)
Psycholinguistics has provided numerous theories that explain how a person acquires a language, produces and perceives both spoken and written language, including theories of proceduralization. Learners of English as a foreign language (hereafter referred to as EFL learners)EFL learners often find it difficult to achieve oral fluency, a key construct closely related to the mental state or even mental health of learners. According to previous research, this problem could be addressed by the mastery of formulaic sequences, since the employment of formulaic sequences could often promote oral fluency in the long run, reflected in the positive relationship between formulaic sequence use and oral fluency. However, there are also findings contradicting the abovementioned ones, without adequate explanations. The present This study aims to explore the roles of formulaic sequences in oral fluency, taking into account the relationship between formulaic sequence use and oral fluency. This study investigated 120 pieces of spoken narratives by Chinese EFL learners’ performance in spoken narratives, using both quantitative and qualitative methods, combined with artificial intelligence techniques, to explore the roles of formulaic sequences in oral fluency, taking into account the relationship between formulaic sequence use and oral fluency. Results of canonical correlation analysis showed that the frequency of formulaic sequences was significantly related to speed fluency (r=0.563, p=0.000) and breakdown fluency (r=0.360, p=0.001), while the variety of formulaic sequences was significantly related to repair fluency (r=0.292, p=0.035). Case studies further demonstrated that formulaic sequences could contribute to oral fluency development by promoting speed and reduce reducing pausing when retrieved holistically, but they sometimes lost processing advantages when retrieved and processed in a word-by-word manner. The inappropriate use of formulaic sequences also neutralized the facilitative effects of formulaic sequences on repair fluency and could mirror speakers’ occasional tendency to sacrifice repair fluency for the improvement of speed and breakdown fluency when using formulaic sequences. Pedagogical implications were provided accordingly to promote sustainable oral fluency development through the use of formulaic sequences.